2014
DOI: 10.1111/aos.12553
|View full text |Cite
|
Sign up to set email alerts
|

Retinal hemodynamic oxygen reactivity assessed by perfusion velocity, blood oximetry and vessel diameter measurements

Abstract: ABSTRACT.Purpose: To test the oxygen reactivity of a fundus photographic method of measuring macular perfusion velocity and to integrate macular perfusion velocities with measurements of retinal vessel diameters and blood oxygen saturation. Methods: Sixteen eyes in 16 healthy volunteers were studied at two examination sessions using motion-contrast velocimetry and retinal oximetry with vessel diameter corrections. To test oxygen reactivity, participants were examined during normoxia, after 15 min of hyperoxia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 66 publications
3
30
1
Order By: Relevance
“…Of the 12 available previously published studies that measured the BFV of healthy eyes with the RFI, 9 studies used the 20-degree FOV [1, 4, 1114, 16, 17, 24], which yielded arteriolar BFVs ranging from 3.15 to 4.45 mm/s and venular BFVs ranging from 2.50 to 3.20 mm/s. On the other hand, 4 studies used the 35-degree FOV [1821], which yielded arteriolar BFVs ranging from 3.16 to 4.70 mm/s and venular BFVs ranging from 3.15 to 3.20 mm/s.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 12 available previously published studies that measured the BFV of healthy eyes with the RFI, 9 studies used the 20-degree FOV [1, 4, 1114, 16, 17, 24], which yielded arteriolar BFVs ranging from 3.15 to 4.45 mm/s and venular BFVs ranging from 2.50 to 3.20 mm/s. On the other hand, 4 studies used the 35-degree FOV [1821], which yielded arteriolar BFVs ranging from 3.16 to 4.70 mm/s and venular BFVs ranging from 3.15 to 3.20 mm/s.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the 35-degree FOVs were acquired and followed by the 20-degree FOVs. Klefter et al reported the short-term variability with the LoA up to 1.1 mm/s [16]. Further studies are needed to test the repeatabilities with different FOVs in different imaging orders which may validate the viewpoint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Linsenmeier, 1986; Linsenmeier and Braun, 1992; Pournaras, 1995; Wanek et al, 2012; Yu and Cringle, 2001) However, the validity of this assumption is questionable in the inner retina except under certain experimental conditions. (Alder et al, 1990; Braun et al, 1995) Methods to assess retinal oxygenation including MRI and oximetry have yielded great contributions to our understanding of retinal oxygenation, (Choudhary et al, 2013; Hammer et al, 2009; Hardarson, 2013; Kashani et al, 2014; Klefter et al, 2014; Man et al, 2013; Shahidi et al, 2013; Trick and Berkowitz, 2005; Yi et al, 2013; Zhang et al, 2011) but these do not quantify MO 2 . Recently, Palkovits and coworkers have published results obtained by the combined use of retinal vascular oximetry, vessel caliber analysis and blood velocity measurements using laser Doppler velocimetry in healthy subjects.…”
Section: 0 Discussionmentioning
confidence: 99%
“…18 RFI is cleared by the US Food and Drug Administration (FDA). 19 The system uses hemoglobin in red blood cells as the intrinsic motion contrast agent for measuring the velocity of the red blood cells in retinal arterioles and venules. No contrast agent is needed and therefore the method is non-invasive.…”
Section: Methodsmentioning
confidence: 99%